Predictors of mushroom production in the European temperate mixed deciduous forest - Stojek, Katarzyna; Gillerot, Loïc; Jaroszewicz, Bogdan (Forest ecology and management, 2022)
•We studied mushroom productivity on plots with different tree richness and composition.•The interaction between precipitation and temperature modulated mushroom production.•Mushroom production was enhanced by mushrooms species richness.•Ectomycorrhizal species richness was mainly affected by stand characteristics.•Species richness of saprotrophic mushrooms was affected by pH of the soil. Mushrooms play an important role in the maintenance of ecosystem processes and delivering ecosystem services, including food supply. They are also an important source of income for many people worldwide. Thus, understanding which environmental factors influence mushroom productivity is a high practical and scientific priority. We monitored the production of mushrooms in temperate mixed deciduous forest in Białowieża Primeval Forest in eastern Poland for two yielding seasons. The research plots were set under similar environmental conditions (topography, geology, soil type) but differed by tree species composition and tree species richness. The main factor explaining mushroom production (close to 35% of the variation explained by the model) was the species richness of mushrooms. In turn, the species richness of mushrooms was mainly explained by soil properties (pH and C/N ratio) and stand characteristics (including tree species richness and wood increment) for ectomycorrhizal mushrooms and by soil pH for saprotrophic mushrooms. Higher precipitation in 2021 resulted in higher mushroom production than in 2020, while low levels of precipitation in 2020 resulted in stronger effect of ambient temperature. The differences in mushroom yield between years varied highly among plots. They were explained by stand characteristics, and in the case of saprotrophic mushrooms by tree richness and their own species richness. Our results suggest that promoting mushroom species richness is fundamental for increasing mushroom yield and should be taken into account in forest management.